IMAGERY AND CONNOTATIVE MEANING FOUND IN SONG LYRICS OF TAYLOR SWIFT’S FOLKLORE - Annisa, Astri; Nitisari, Dwi (UG Journal, 2024)
This research focuses on analyzing imagery and connotative meaning found in song lyrics of Taylor Swift’s Folklore. The aims of this research are to find out the types of imagery used in song lyrics of Taylor Swift’s Folklore also to find out the types of connotative meaning from the imagery found in song lyrics of Taylor Swift’s Folklore. This research analyzed the seven types of imagery utilizing Thomas R. Arp and Greg Johnson’s (2017) theory and will go in-depth analyzing its meaning by using the three types of connotative meaning proposed by Riebs & Reeves’s (2005). The research method used in this research is a qualitative method. From this research, out of 138 data the researchers found all 7 types of imagery used in the lyrics of Taylor Swift’s Folklore. Those seven types of imagery are visual imagery (50 data), auditory imagery (11 data), olfactory imagery (1 datum), gustatory imagery (1 datum), tactile imagery (7 data), organic imagery (25 data), and kinesthetic imagery (43 data). The researchers also found there are 3 types of connotative meaning used in imagery found from the lyrics of Taylor Swift’s Folklore. Those three types of connotative meaning namely positive (47 data), negative (66 data), dan neutral (25 data).